Efficacy and safety of Nirmatrelvir/Ritonavir for treating the Omicron variant of COVID-19 - Qiu, Chaochao; Wu, Zhengxing; Liu, Xiaojing; Zhang, Qiang; Wu, Lianpeng; Ye, Xinchun; Zhou, Jiajun; Shi, Jichan; Jiang, Xiangao (Frontiers in Medicine, 2023)
Objective To evaluate the efficacy and safety of Nirmatrelvir/Ritonavir in the treatment of the Omicron variant of coronavirus disease 2019 (COVID-19). Methods Data from 58 patients who were infected with the Omicron variant of COVID-19 were retrospectively collected. The patients were divided into two groups according to the treatment regimen they received. Patients in both groups were given Lianhua Qingwen capsules orally, three times/day, 6 g/time. The study group was given Nirmatrelvir 300 mg/Ritonavir 100 mg orally, q12h, for 5 days, and the control group was not given any antiviral drugs. The two groups were compared in terms of the change in computed tomography (CT) values of COVID-19 nucleic acid, the negative conversion time of COVID-19 RNA, hospitalization time, adverse drug reactions and COVID-19 nucleic acid re-positive tests. Results The time to increase the CT values in the study group was faster than that in the control group, and the CT values in the study group were significantly larger than in the control group on days four and seven (p < 0.05); The negative conversion time in the study group was shorter than the control group (Z = –2.424, p = 0.015), and the hospitalization time was also shorter (Z = –2.603, p = 0.009). There were no statistically significant adverse drug reactions during hospitalization in both groups (χ2 = 2.747, p = 0.097). None of the study group tested re-positive for SARS-CoV-2 nucleic acid after discharge. Conclusion The efficacy of Nirmatrelvir/Ritonavir in the treatment of the Omicron variant of COVID-19 was positive and had good tolerance in patients.